Jigagem de óxidos de ferro proveniente do rejeito da produção de rocha fosfática para produção de pigmentos - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The importance of pigments to human civilization is evident and well documented. Although these materials were discovered many years ago, research continues to this day, industries often require new colors and more reproducible and stable shades. The selection of raw materials is of paramount importance in order to acquire high quality mineral pigments, color luminescence and purity, free of chemical contaminants. Mineral pigments have been gaining commercial acceptance as a result of growing ecological awareness, which aims to reduce the environmental impact of synthetic production methods. The most common mineral pigments are iron oxides, manganite, chromite, quartz, feldspar, monazite, zirconite, titanite muscovite and biotite. Most of the iron production in Brazil, whether processing the hematite or magnetite, is done by flotation and magnetic separation. Flotation impairs the use of oxides for purposes other than steel production due to the huge amount of chemicals, mainly surfactants, involved in this step. Jigging is a process of hydraulic separation consisting of the repeated expansion and vertical contraction of a bed of particles by the pulsating movement of water. The result of this movement is the stratification of the material. Anglo American Phosphates from Brazil has a tailings production of 2 Mt (million tons) with barite contents of 6% and magnetite about 40%, and this material is sent in full to the tailings dam. The removal of the magnetite from the phosphate production process leads to three major gains: the first would be the reduction of material sent to the flotation steps of barite and apatite, the second is the generation of a material that could be used for other purposes, such as The production of pigments, with the generation of a co-product and the third would be the reduction of material sent to the tailings dam, thus avoiding the construction of new dams and reducing environmental impacts. The enrichment of the reject by the jigging for the extraction of this mineral is justified due to the specific mass difference of the minerals involved, together with the simplicity of operation and its low operating cost. Concentration by gravimetric methods, based on the density difference between magnetite and quartz, may be an option for the use of the reject of the phosphate rock production for the production of high-grade magnetite to be used in the production of pigments. The results show that it is possible to separate magnetite for the purpose of producing pigments in certain parameters of jigue operation.
Iron oxide jigging from the reject of phosphate rock production for pigment manufacturing
Keywords: Minério de ferro; Jigagem; Rejeito; Fosfato; Pigmentos; Iron ore; Jigging; Cphosphate; Pigments; GERENCIA DE PRODUCAO::PLANEJAMENTO, PROJETO E CONTROLE DE SISTEMAS DE PRODUCAO